Latent Class Analysis of Professional Competence, Active Faith, Selfless Service, Social Responsibility and Balanced Lifestyle of Senior College Students during COVID-19 Pandemic - Balila, Jolly S.; Balila, Edwin A. (8ISC Abstract Proceedings, 2022)
The institutional learning outcomes are designed to guide the university-developed students’ learning outcomes and to help shape their decision-making processes. However, due to the COVID-19 pandemic, institutional learning outcomes can be affected. This study investigates Latent Class classifications of Professional Competence, Active Faith, Selfless Service, Social Responsibility, and Balanced Lifestyle (PASSB) using validated questionnaires. This survey was conducted to 396 graduating college students in a faith-based university during the academic year 2019-2020. The SPSS version 25 was used to conduct the latent class analysis (LCA). The PASSB was designed primarily to group the respondents into two latent classes. Latent Classes 1 and 2 consist of respondents whose PASSB were not developed and developed respectively during their stay in the university. Professional Competence (PA), Active Faith (AF), Selfless Service (SR), Social Responsibility (SR), and Balanced Lifestyle (BA) have respectively 14, 12, 6, 8, and 14 items. The results show that 17.3% of students whose Professional Competence was not developed and 82.7% were developed during their stay in the university. A considerable proportion of graduating seniors whose Active faith (13.6%), Selfless Service (86.3%), Social Responsibility (84.2%), and Balanced lifestyle (24.5%) were not developed upon exiting the portal of the university. It is recommended to review the institutional outcomes considering the new normal. Further study is recommended since a higher proportion of graduating students have not developed Selfless Service and Social Responsibility upon exiting the portal of the university. The Covid-19 pandemic might have contributed to these results. Keywords : Latent Class Analysis, Professional Competence, Active Faith, Selfless Service, Social Responsibility and Balanced Lifestyle (PASSB)